Theoretical and numerical study of pulsating developing flow in circular tubes - Lee, Shiang Long (2009)
Many flows of practical importance are unsteady. These include flows over aircraft, rotorcraft, and turbomachines. In many cases, these unsteady flows are also turbulent, compressible and three-dimensional. These complicated flow characteristics and the lack of reliable experimental data and analysis have rendered the nature of unsteady flows constitute one of the least understood problems in fluid mechanics. Among unsteady flows, the unsteady internal flows are of much practical interest. Applications can readily be found in duct flows, flows in manifolds of engines and blood flow in veins etc [1].